The effect of management control on labour productivity of labour-intensive works in Ghana - Bamfo-Agyei, Emmanuel; Thwala, Didibhuku; Aigbavboa, Clinton (Acta Structilia, 2022)
In Ghana, many construction projects end in dispute, because contractors are unable to meet the completion time. As many construction operations are labour intensive, the question of labour productivity becomes paramount, especially as higher productivity levels usually translate into superior profitability, competitiveness, and income. This article aims to examine the management control factors affecting construction labour productivity in Ghanaian construction firms. It assesses the measuring techniques that are used to improve labour productivity in the construction firms. The article also determines the relationship between management control and labour productivity on labour-intensive works in Ghanaian construction firms. The study adopted a quantitative research design that used a questionnaire-based descriptive survey. Records available at the Ghana Social Opportunity Project (GSOP) indicate that 920 professionals are involved in labour-intensive works on road infrastructure. A purposive sampling technique was used to select 40 districts involved in road construction projects; 560 respondents were considered for the study. The summary of the data consisted of means, standard deviations, percentages, cross-tabulations, and frequencies. Principal axis factor analysis revealed three (3) components with eigenvalues above 1 that may influence labour productivity of labour-intensive works on road construction. These components are effective communication, supervision technique, and design inadequacies. Construction managers must monitor workforce performance by ensuring that the three factors influencing management control are considered.